Cytokine and nitric oxide production in an adult patient with staphylococcal scalded skin syndrome. - Castellano, Lúcio Roberto; Silva-Teixeira, David Nascimento; Antonelli, Élida J; Rodrigues Junior, Virmondes; Cavalcanti-Cordeiro, Maria Bernarda (Investigación Clínica, 2009)
Staphylococcal scalded-skin syndrome (SSSS) is an exfoliative dermatitis resultant from the infection with exfoliative-toxin-producing (ET) Staphylococcus aureus. This syndrome usually occurs in children, while adult cases are generally linked to renal-deficiency or immunossupresion. A case of a 74 years old woman presenting SSSS after hospital admission due to cardiovascular disorders is presented and discussed. Cytokines (TNF-_, IFN-_, IL-6, IL-13 and IL-10) and nitric oxide (NO) production in vitro by whole blood leukocytes (WBL) were investigated. Leukocytes stimulated by lipopolysaccharide or phytohemagglutinin produced increased IFN-_, TNF-_, IL-13 and NO levels after treatment. Based on these results, immunological aspects of the disease are discussed.